2018
DOI: 10.1101/481168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and validation of serological markers for detecting recent exposure toPlasmodium vivaxinfection

Abstract: One Sentence Summary: The manuscript describes identification and validation of a novel panel of P. vivax proteins that can be used to detect recent exposure to P. vivax infections within the prior 9 months.Abstract: In order to accelerate towards malaria elimination, improved targeting of limited resources is essential. A major gap in our elimination toolkit for Plasmodium vivax malaria is the identification of individuals carrying arrested liver stages, called hypnozoites. These clinically silent but frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…There is also substantial between-individual variation in the antibody response generated following SARS-CoV-2 infection. By measuring multiple biomarkers in large numbers of individuals, it is possible to create a serological signature of previous infection [17][18][19]. Although necessarily more complex than a single measured antibody response, such an approach has the potential of providing more accurate classification and being more stable over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also substantial between-individual variation in the antibody response generated following SARS-CoV-2 infection. By measuring multiple biomarkers in large numbers of individuals, it is possible to create a serological signature of previous infection [17][18][19]. Although necessarily more complex than a single measured antibody response, such an approach has the potential of providing more accurate classification and being more stable over time.…”
Section: Discussionmentioning
confidence: 99%
“…Measured antibody responses to multiple antigens can be combined to identify individuals with previous SARS-CoV-2 infection using classification algorithms. Here we use a random forests algorithm [17].…”
Section: Statistical Evaluation Of Diagnostic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…different rates of acquisition, boosting, and decay, and researchers have now started to study these antibody kinetic profiles for many antibodies to P. falciparum and P. vivax , and to characterize their suitability for estimating recent exposure in different age groups and transmission settings 23 . Several ongoing efforts are using this information to identify antibody signatures that are reliable, quantitative measures of recent exposure to malaria parasites 2428 . In parallel with biomarker identification, antigen production methods, analytics and technology platforms have advanced sufficiently to generate malaria antibody assays that will be field deployable in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that combining antibody responses to multiple targets more accurately reflects recent malaria infection than to one antigen though at small increments 4,31,32 . The fact that this study showed that multiplex antimalarial antibody data could be collected accurately at scale aids in ensuring representation of the variation in human immune responses.…”
mentioning
confidence: 99%